Regency buck ebook - Heyer, Georgette (Alastair-Audley, 2008)
An altogether unsatisfactory arrangement After their father's death, Miss Judith Taverner and her brother Peregrine travel to London to meet their guardian, Lord Worth, expecting an elderly gentleman. To their surprise and utter disgust, their guardian is not much older than they are, doesn't want the office of guardian any more than they want him, and is determined to thwart all their interests and return them to the country. With altogether too many complications But when Miss Taverner and Peregrine begin to move in the highest social circles, Lord Worth cannot help but entangle himself with his adventuresome wards... Praise for Regency Buck: "Clever!"— Library Journal "Georgette Heyer is unbeatable."— Sunday Telegraph "Light and frothy, in the vein of the author's other Regency novels, this follows the fortunes of Miss Judith Taverner and her brother, Sir Peregrine. A good introduction to Heyer's period stories..." — The Booklist "Reading Georgette Heyer is the next best thing to reading Jane Austen."— Publishers Weekly "A writer of great wit and style... I've read her books to ragged shreds"— Katie Fenton, Daily Telegraph "Wonderful characters, elegant, witty writing, perfect period detail, and rapturously romantic. Georgette Heyer achieves what the rest of us only aspire too."— Katie Fforde